BEYOND AN “UNDEFILED PRIVILEGE”. POLITICAL-RELIGIOUS STRUGGLES IN THE PROMULGATION OF THE DOGMA OF THE IMMACULATE CONCEPTION IN MEXICO AND SPAIN, 1854-1855 (Tzintzun, Revista de Estudios Históricos, 2024)
The promulgation of the bull Ineffabilis Deus in 1854 and with it the elevation ofthe mystery of the Immaculate Conception to dogma, constituted the prelude tothe dogmatic proclamation of papal infallibility in 1870. The objective of thistext is to analyze in a comparative way the political-religious scenarios that ruledboth in Mexico and Spain and their transcendence for the Pase Regio or the PaseNacional of this important bull that, theologically, put an end to the old spiritualdiscussions about the pure nature of Mary, but politically, it was the combativematerialization of the papacy to recover its questioned temporal power.
Keywords: Ineffabilis Deus; Dogma of the Immaculate Conception; Dictatorship of Santa Anna; Progressive Biennium